Gender Equity in Higher Education - Bushra , Dr. Bushra; Akbar , Ms. Tahira; Qamar, Ms. Yasmeen (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
In this article we discussed about gender equity in higher education, women facing gender disparity especially in higher secondary education Women have been subjected to marginalization and various kinds of discrimination since ancient times. Additionally, it seeks to discuss the concept of gender inequity all over the world and also highlighted Pakistani education system facing gender disparity especially in rural areas. Then later on provide steps towards reduce gender disparity. This paper also discuss the concept of Gender equity in education in the light of the Holy Quran and the Sunnah. The famous hadith “acquisition of knowledge is binding on all Muslims” make it clear that education in Islam is equally important, irrespective of the sex. It concludes that Islam doesn’t restrict women from getting education, it will also briefly explore the current situation of women education in Pakistan, and provide ways to improve their education standards. Main objective of this article is that men and women should be treated equally according to their respective needs especially in higher education because they are actually facing disparity. In the last discussed about normative teachings of Islam with regard to the standing and role of women in society as the criteria by which to judge the practice of Muslims and to evaluate their compliance with Islam.